Chalcogenia brandli sp. nov. from Ethiopia (Coleoptera: Buprestidae: Anthaxiini) - Bílý, Svatopluk (Zootaxa, 2018)
Chalcogenia brandli sp. nov. from Ethiopia is described, illustrated and compared with the most similar species, and attributed to the Chalcogenia sulcipennis species-group within the genus Chalcogenia.